Analisis Pemilihan Supplier pada Toko Akbar Telur dengan Menggunakan Metode AHP - Kumala Zahra, Siti; Saadatu Daroen, Siti; Andini, Winda; Azizah Seviyanti, Sindy; Septenia Sitepu, Aisyah; Oktariza, Wawan (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2024)
Eggs are an important source of animal protein as they contain high quality protein and have high biological value. Egg consumption in Indonesia continues to increase every year. This creates opportunities and competition in the egg market, including in Bogor City. In this context, the selection of the right supplier is key in meeting market demand and increasing the existence of sellers. This research was conducted at Shop Akbar Telur in Bogor Suryakencana Market. Data was collected through direct observation and interviews with the shop owner. The AHP method was used to process qualitative and quantitative data to prioritize suppliers based on price, quality and quantity criteria. The results of the analysis using AHP show that price is the highest criterion in selecting egg suppliers at Akbar Telur, followed by quality and quantity. Suppliers with the highest value for each criterion are SJT1 (price), SJT1 (quality), and SJT1 (quantity). The consistency level of criteria comparison is also acceptable. In selecting egg suppliers, the recommended overall priorities are SJT1, SJT2, and SB. The results of this study contribute to the understanding of supplier selection strategies that can improve store efficiency and performance.